THE ROLE OF CYTOKINE SYSTEM RANKL-RANK-OPG AND CATHEPSIN K IN THE PATHOGENESIS OF OSTEOPOROSIS: ACHIEVEMENTS AND PERSPECTIVES IN THE TREATMENT OF DISEASE - S. Sagalovsky; P. Kunze; M. Schönert (Klinicist)
The article presents review of literature dedicated to the contemporary view on the cellular-molecular mechanisms of the bone remodeling and pathogenesis of the osteoporosis. The discovery of the cytokine RANKL-RANK-OPG system and significant role of the cathepsin K in process bone remodeling has made progress in understanding the mechanisms development disease and possible to development drugs of the new generation – denosumab, a fully human RANKL monoclonal antibody and inhibitor cathepsin K odanacatib that inhibits of the bone resorption.